1995
DOI: 10.1126/science.7754374
|View full text |Cite
|
Sign up to set email alerts
|

KAI1 , a Metastasis Suppressor Gene for Prostate Cancer on Human Chromosome 11p11.2

Abstract: A gene from human chromosome 11 p11.2 was isolated and was shown to suppress metastasis when introduced into rat AT6.1 prostate cancer cells. Expression of this gene, designated KA11, was reduced in human cell lines derived from metastatic prostate tumors. KA11 specifies a protein of 267 amino acids, with four hydrophobic and presumably transmembrane domains and one large extracellular hydrophilic domain with three potential N-glycosylation sites. KA11 is evolutionarily conserved, is expressed in many human ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
561
1
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 686 publications
(576 citation statements)
references
References 24 publications
12
561
1
2
Order By: Relevance
“…Evaluation of KAI1 mRNA expression in relation with clinical parameters of pancreatic cancer patients revealed that the levels of KAI1 mRNA expression is signi®cantly down-regulated in pancreatic cancer patients with advanced tumor stages with lymph node metastasis compared with those without it (Guo et al, 1996). These observations and the broad tissue distribution of KAI1 message (Dong et al, 1995) suggest a more universal role of KAI1 as a metastasis suppressor. Normal small intestine and colon tissues were found to express KAI1 message (Dong et al, 1995), but there have been no reports on the expression and functional analyses of KAI1 in gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Evaluation of KAI1 mRNA expression in relation with clinical parameters of pancreatic cancer patients revealed that the levels of KAI1 mRNA expression is signi®cantly down-regulated in pancreatic cancer patients with advanced tumor stages with lymph node metastasis compared with those without it (Guo et al, 1996). These observations and the broad tissue distribution of KAI1 message (Dong et al, 1995) suggest a more universal role of KAI1 as a metastasis suppressor. Normal small intestine and colon tissues were found to express KAI1 message (Dong et al, 1995), but there have been no reports on the expression and functional analyses of KAI1 in gastrointestinal cancers.…”
Section: Discussionmentioning
confidence: 83%
“…They also showed that the introduction of KAI1 gene by microcell-mediated chromosome transfer method resulted in no e ect on their metastatic ability of highly metastatic rat mammary cancer cells despite the certain amounts of KAI1 expression (Rinker-Schae er et al, 1994; Dong et al, 1995). Furthermore, a recent immunohistochemical study has shown that the presence of KAI1 protein in prostate cancer has a negatively correlated with advanced clinical stages (Ueda et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmembrane protein CD82 is directly associated with the epidermal growth factor receptor (EGFR) and other tyrosine kinase receptors and accelerates desensitisation of tyrosine receptor induced signalling correlated with an increased rate of receptor endocytosis (Odintsova et al, 2000). This attenuation of EGFR signalling by CD82 explains for its recently identified role as metastasis suppressor gene for prostate and pancreatic cancer (Dong et al, 1995;Guo et al, 1996). In addi- For cDNA array analysis each spot was defined by positioning of a grid of circles over the array image; spot density for each gene was measured using Array-Vision software (Version 5.1, Imaging Research, Canada).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…The age-related death rate for prostate cancer has been roughly constant over the past several decades. The causes of prostate cancer remain obscure; both environmental factors and genetic predisposition may contribute to developing the disease (Dong et al, 1995;Pienta and Esper, 1993).…”
Section: Introductionmentioning
confidence: 99%